En kvantitativ utvärdering av ett lågenergihus i subarktiskt klimat : – gällande energianvändning, inomhusklimat och fuktvandring - Gustavsson, Jonathan (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2020)
Low-energy houses are a good concept for reducing energy use during the building's use. Especially when studies have shown economic profitability in buildings that meet the requirements for the definition of low-energy houses - that the energy performance is at least 25% better than the building standard from the Swedish National Board of Housing, Building and Planning. The investment cost of houses with low energy performance is higher, but the economic profitability is achieved under the reduced operating costs. However, it can be difficult to ensure the quality of all new construction techniques and installations, which can lead to worse energy performance than projected values show. To maintain economic profitability, buildings must be maintained throughout their lifetime without unexpected costs to a greater extent. Moisture damage, which can seriously damage the construction and add odors that lead to a bad indoor climate, has over time caused great costs in our buildings. Poor indoor climate can have consequences that create or strengthen mental and physical symptoms. This is something we want to counteract with knowledge of how the indoor climate is in use. In Sweden, most evaluations of low-energy houses have treated houses in the southern parts of the country. There are large climate differences across the country. Construction techniques that are proven to work in the south, do not always perform as well in the north. In the northernmost parts, there is a subarctic climate - where the average temperature exceeds for a maximum of three months a year. The purpose of this study is to evaluate a low-energy house in a subarctic climate and make a contribution to increased knowledge regarding the type of building in this climate. To achieve the project's goal, to map the house's performance in terms of energy use, indoor climate and moisture migration, literature and case studies have been carried out. These studies are aimed at one of four apartment buildings that are located in the northernmost parts of ...